EFFECTIVENESS OF 3S-BASED NURSING DOCUMENTATION TRAINING (SDKI, SLKI, SIKI) ON NURSES’ KNOWLEDGE, PERFORMANCE, AND DOCUMENTATION SKILLS - Wisuda, Aris Citra; Citra Suraya; Miming Oxyandi; Raden Surahmat; Muhamad Andika Sasmita Saputra; Helsy Desvitasari (Citra Internasional Institute, 2025)
Accurate and comprehensive nursing documentation is essential for ensuring continuity of care, legal accountability, and quality outcomes. However, many nurses face challenges in implementing standardized documentation practices. The 3S-based framework comprising SDKI (Standar Diagnosis Keperawatan Indonesia), SLKI (Standar Luaran Keperawatan Indonesia), and SIKI (Standar Intervensi Keperawatan Indonesia) has been developed to enhance the quality and consistency of nursing records. This study aimed to evaluate the effectiveness of 3S-based nursing documentation training on nurses’ knowledge, performance, and documentation skills. A quasi-experimental design with a pretest-posttest approach was conducted at two hospitals: RSUD Sungaililin in December 2024 and RSUD Bayung Lencir in April 2025. A total of 80 nurses participated, with 40 respondents from each hospital. The intervention consisted of structured training sessions on the 3S documentation model. Data were collected using validated questionnaires and observation checklists, and were analyzed using paired and independent t-tests to assess changes before and after the intervention. The findings showed a significant improvement in nurses’ knowledge, performance, and documentation skills following the training (p < 0.05). Both hospitals demonstrated consistent positive outcomes, indicating the effectiveness of the 3S-based training regardless of setting. The 3S-based documentation training significantly enhances nurses’ competencies in recording patient care. These results support the integration of structured documentation models into nursing education and hospital in-service training programs to improve care quality and documentation practices.